2018
DOI: 10.1016/j.ecoenv.2017.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate-based herbicides toxicity on life history parameters of zoophytophagous Podisus nigrispinus (Heteroptera: Pentatomidae)

Abstract: The increase of agricultural areas with glyphosate-resistant (GR) crops, and use of this herbicide in Brazil, makes necessary to assess its impacts on non-target organisms. The objective was to evaluate the development, reproduction and life table parameters of Podisus nigrispinus (Heteroptera: Pentatomidae) reared on GR-soybean plants treated with glyphosate formulations (Zapp-Qi, Roundup-Transorb-R and Roundup-Original) at the recommended field dose (720g acid equivalent ha). Glyphosate formulations had no a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
(52 reference statements)
0
3
0
2
Order By: Relevance
“…Adverse effects of glyphosate have been found on several animal species, including honey bees. Although the mode of action of this herbicide in insects is still unknown, parameters affected include development, reproduction, navigation, gustatory perception and olfactory learning (Balbuena et al, 2015;Helmer et al, 2015;Herbert et al, 2014;Thompson et al, 2014;Zanuncio et al, 2018). Therefore, it is reasonable to worry about its influence on pollinators.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse effects of glyphosate have been found on several animal species, including honey bees. Although the mode of action of this herbicide in insects is still unknown, parameters affected include development, reproduction, navigation, gustatory perception and olfactory learning (Balbuena et al, 2015;Helmer et al, 2015;Herbert et al, 2014;Thompson et al, 2014;Zanuncio et al, 2018). Therefore, it is reasonable to worry about its influence on pollinators.…”
Section: Introductionmentioning
confidence: 99%
“…Robust studies have shown that the active principle of pure glyphosate can have impacts on soil fauna, but not the formulations 72 and vice versa, i.e., results are often divergent. Different formulations of potassium salt and/or isopropylamine salt of glyphosate did not cause side effects on the predator Podisus nigrispinus 73 . However, some adjuvants led to more harmful outcomes than glyphosate itself.…”
Section: Glyphosate Banmentioning
confidence: 95%
“…The effect of herbicides on insect populations in maize fields should be considered in integrated pest management (IPM), since the molecules of these chemicals can have deleterious effects on arthropod species, including beneficial insects (de Menezes & Soares, 2016;Zanuncio et al, 2018). However, the interactions of different herbicides with different crop genotypes and insect species are particular (De Souza et al, 2020), making it difficult to obtain accurate information on the subject.…”
Section: Introductionmentioning
confidence: 99%